Evaluation of the Immune Effect of a Trivalent Fowl Adenovirus Inactivated Vaccine Against FAdV-4/8a/8b - Yulan Jiao; Qianhui Zhao; Yulong Zhao; Yingjie Li; Sumin Pan; Yinming Li; Yuntao Liu; Wanyu Shi (Veterinary Sciences, 2025)
Fowl adenovirus can cause various diseases such as hepatitis-hydropericardium syndrome (HHS) and inclusion body hepatitis (IBH), which leads to huge economic losses for China’s poultry industry. In recent years, the prevalence of FAdV-4, FAdV-8a, and FAdV-8b has been on the rise. In this study, a trivalent fowl adenovirus inactivated vaccine against FAdV-4/8a/8b was generated and the immune effect was evaluated. The results showed that chickens immunized with the trivalent vaccine could effectively resist the challenge of virulent strains of FAdV-4, FAdV-8a, and FAdV-8b. All chickens in the immunized groups survived after virus injection, gained weight normally, and the lesions in tissues and organs (liver, spleen, kidney, etc.) were significantly decreased compared with the control group. The viral load in the liver of the immunized group was significantly lower than that of the challenge control group five days after the challenge (p < 0.01), and the cloacal excretion was significantly lower than that of the non-immune control group (p < 0.01). Moreover, until 16 weeks after immunization, the neutralizing antibody level against FAdV-4, FAdV-8a, and FAdV-8b remained above 8.27 log2. As a result, the trivalent vaccine generated in our study was an attractive candidate to prevent and reduce the spread of HHS and IBH in China’s poultry industry.